Intraoperative optical coherence tomography angiography for intraocular surgery - Cheng, Dan; Zhang, Ziyi; Qiao, Yilin; Ye, Yufeng; Zhu, Xueying; Ruan, Kaiming; Shen, Meixiao; Liu, Kaiyuan; Tao, Jiwei; Chen, Yiqi; Shen, Lijun; Li, Peng (Frontiers in Physics, 2023)
Purpose: To evaluate the feasibility of an intraoperative optical coherence tomography angiography (iOCTA) system integrated with a surgical microscope, and further investigate the real-time retinal vascular change in intraocular pressure fluctuation during surgery in rabbits. Methods: The feasibility of this system was confirmed through fundus angiography imaging in 12 rabbit eyes during simulated surgeries in 4 groups, 30 mmHg infusion pressure (IP), 60 mmHg IP, 100 mmHg IP, and control groups. The eyes were removed after seven days. Retinal ganglion cell (RGC) damage was analyzed histologically. Results: The OCTA technique can acquire images of retinal capillaries in rabbit eyes and quantitatively analyzing the vessel density. In the 30 mmHg IP group, there was no significant difference in the retinal vasculature during the operation. The OCTA signal and the RGCs decreased significantly in the 60 and 100 mmHg groups. Conclusions: The system can real-timely monitor the human retinal vasculature in high-resolution images and help surgeons to make decision during intraocular surgery.